The Integrated System Design Of Sales And Production Module Using RAD Method - Alvin Dzaki Hernindyaputra; Monika Evelin Johan; David Tjahjana (Universitas Multimedia Nusantara, 2023)
PT Shafira Putri Kreatif is a company engaged in the field of fashion and apparel for men and women. In business processes, communication is carried out manually in the form of face-to-face or in-office meetings between subsidiaries. This results in inappropriate or forgotten information on production and sales. Therefore, implementing the ERP module is because it can help find important problem points faced by companies to better control the company's financial performance. The SDLC Rapid Application Development (RAD) method was used. System design is done by making DFD and ERD. The system design is coded using the PHP programming language with the Laravel framework and SQL database. The result of the research is a website-based application that is integrated with the sales module which can assist in viewing and managing transaction data from subsidiaries.